The Effectiveness of Implementing Team-Based Learning in Improving Learning Outcomes of Nursing Students: Literature Review - R. Sapeni, Muhammad Al-Amin; Hasriana, Hasriana; Handayani, Fitriya; Mulyati, Mulyati; Yunus, Suwardha; Lukman, Sartika; Suardi, Asrifah (Indonesian Journal of Global Health Research, 2024)
Learning methods are considered to be a factor in improving nursing student learning outcomes. The pedagogy currently used greatly limits the role of students in taking an active role in class, has high costs, and limits the number of student ratios. Learning methods are needed that can increase student interest in class, and work together in teams, and are able to influence academic performance, such as the Team-Based Learning (TBL) method. Objective: To evaluate the effectiveness of implementing TBL in improving nursing students learning outcomes. Method: The design of this research is a literature review. Article searches used Pubmed, Proquest, ScienceDirect, Cochrane Library, and Scopus databases. The research questions are structured using the PICO method, and keywords are based on Boolean combinations. There were 4083 articles found, and only 6 articles included were in accordance with the research questions. published from 2016-2021. Results: The results of critical analysis of articles that include the application of TBL to nursing students can significantly improve academic achievement, knowledge, clinical performance, learning attitudes, problem solving, critical thinking, learning attitudes, and learning experiences. Conclusion: Implementing TBL can improve nursing students' learning outcomes. Therefore, the TBL method can be recommended in nursing education.